Bed planting for enhancing input use efficiency of crops - Aggarwal, Pramila; Garg, R. N.; Chakraborty, Debashis; Kamble, Kalpana; Singh, Ravender (Indian Farming, 2015)
Bed planting technology should form an important component of the regional strategy for food security, rural development, enhanced profitability, improved environmental quality and sustainability of natural resources. It has the potential to provide opportunities for crop diversification through introduction of vegetables and high value intercrops in maizewheat system. It would thus help farmers to reduce cost of cultivation, increase crop productivity and their profitability.